Membaca Al-Qur’an Lewat Layar: Tafsir Populer dan Pesan Dakwah dalam Film Nussa dan Rarra - Dea Aulia, Mifta; Haitomi, Faisal; Muhammad Arif; Rizkiyadi; Muhammad Iqbal Rahman (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
The advancement of technology has led to a diverse reception of the Qur'an, transcending traditional frameworks and manifesting through social media. This article examines the reception of the Qur'an in the animated film